2012
DOI: 10.1136/sextrans-2011-050452
|View full text |Cite
|
Sign up to set email alerts
|

Where do sexually active female London students go to access healthcare? Evidence from the POPI (Prevention of Pelvic Infection) chlamydia screening trial

Abstract: This is the first UK study of healthcare attendance in multiethnic female students recruited outside healthcare settings. The high attendance in general practice may represent a valuable opportunity for screening for sexually transmitted infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…In the UK, during follow-up of a chlamydia screening study, around four-fifths of women in the study had paid at least one visit to the GP in a 12-month period, but only 14% had visited a specialised genitourinary medicine (GUM) clinic. With increased STI risk, that is, the number of reported sexual partners, women were more likely to have visited a GUM clinic 16. Opportunistic STI testing at the GP is an important tool in STI control in several countries (USA, Sweden and the UK), and could also work in the Netherlands, since annually about 78% of Dutch people visit their GP 17.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, during follow-up of a chlamydia screening study, around four-fifths of women in the study had paid at least one visit to the GP in a 12-month period, but only 14% had visited a specialised genitourinary medicine (GUM) clinic. With increased STI risk, that is, the number of reported sexual partners, women were more likely to have visited a GUM clinic 16. Opportunistic STI testing at the GP is an important tool in STI control in several countries (USA, Sweden and the UK), and could also work in the Netherlands, since annually about 78% of Dutch people visit their GP 17.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects recent research with young people in the UK, which has revealed willingness to undertake STI self-testing, with general practice the most popular test collection point. [19,20] However, there is also evidence that no one type of STI testing service is suitable to all patients: although some people identify general practitioners (GPs) as a preferred site for testing because it could reduce stigma and shame, many others prefer testing in specialist sexual health services because they appreciate the specialist expertise of staff. [23] The survey data suggest that regardless of where STI testing services are located, increased ease of access may increase testing rates, especially given that low perceived susceptibility results in low motivation for testing.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible avenues for interventions include public health messages for the general population, targeted campaigns, and one-to-one discussions in general practice. [17][18][19][20] Although intentions have been shown to predict behaviour, there is not always a direct link between the two. [3][4][5][6] To increase rates of STI testing, it is not enough to simply strengthen intentions: people must also act on these intentions.…”
Section: Discussionmentioning
confidence: 99%
“…A 2001 qualitative study of female GUM clinic attenders by DixonWoods et al identified five prompts for presenting for testing: own symptoms, partner's symptoms, partner's behaviour, own behaviour and health maintenance, including being traced as a contact 12. These prompts are similar to the responses given in the present study.Although most women attend primary care each year, general practitioners may miss opportunities for encouraging testing, even in women at higher risk 13. …”
mentioning
confidence: 99%